Fresno County Bar Association's Annual Judges' Dinner at Bob Crossland's Barn - Watkins, Howard::::::::: (1982)
Members eating dinner at long tables Paul Eisler: facing camera: Thomas Tusan, Jay Johnson, Val Weston